2011
DOI: 10.1111/j.1600-0668.2010.00676.x
|View full text |Cite
|
Sign up to set email alerts
|

Transport of expiratory droplets in an aircraft cabin

Abstract: It is critical to predict the risk of airborne infection to take appropriate measures to control and mitigate the risk. Most of the studies in past either assume a homogenous distribution of contaminants or use steady-state conditions. The present study instead provides information on the transient movement of the droplets exhaled by an index passenger in an aircraft cabin. These droplets may contain active contagious agents and can be potent enough to cause infection. The findings can be used by medical profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
152
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(165 citation statements)
references
References 28 publications
4
152
0
9
Order By: Relevance
“…Therefore, it is important to assess the influence of exhaled droplets on the emission rates of particles from clothed human body measured in this study. Gupta et al (2011) indicated that the typical amount of exhaled droplets for a breath can be set as 525 per breath. The duration of a breath is about 4 s (Gupta et al, 2010).…”
Section: Influence Of Exhaled Dropletsmentioning
confidence: 99%
“…Therefore, it is important to assess the influence of exhaled droplets on the emission rates of particles from clothed human body measured in this study. Gupta et al (2011) indicated that the typical amount of exhaled droplets for a breath can be set as 525 per breath. The duration of a breath is about 4 s (Gupta et al, 2010).…”
Section: Influence Of Exhaled Dropletsmentioning
confidence: 99%
“…One-jet airflow shows the great potential to prevent the direct exposure to a cough. In fact, most of the latex particles were transported within a short distance from the coughing person in the first 30 s and then could be transported to the entire space with a uniform droplet distribution in 4 min (Gupta et al, 2011). As the source location significantly affects the pollutant transport within an aircraft cabin (Yan et al, 2009), the use of downward plane jet to separate the space into a few sub zones may minimize the transport of respirable particles of a cough from the source.…”
Section: Personal Protection Efficiency (Ppe)mentioning
confidence: 99%
“…Chao et al (2008) found that the lateral dispersion behaviour was dominated by the ventilation airflow and the effect of the thermal plume was relatively minor for the 1.5-45 µm droplets with lower supply airflow rate. It is well known that a cough may be one of the prime infectious sources of airborne diseases as it has a high velocity and large quantity of droplets (Gupta et al, 2009(Gupta et al, , 2011. A number of studies have investigated the basic characteristics of a human's cough regarding velocity distribution and size distribution of droplets.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Chao and Wan (2006) and Gao and Niu (2007) used a Lagrangian model to investigate the dispersion of particles in a room with different ventilation modes. Gupta et al (2011a) investigated the dispersion of exhaled droplets in a section of an aircraft cabin with the Lagrangian method. Gao et al (2012) applied a Lagrangian model to study the lock-up phenomenon of exhaled droplets in a room with displacement ventilation.…”
Section: Introductionmentioning
confidence: 99%